Pengaruh Kualitas Produk Dan Brand Image Terhadap Loyalitas Pelanggan (Studi Kasus Pada Konsumen The Don’s House Di Kota Metro) - Darmawan; Jati Imantoro; Nia Rosita Wati (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study uses quantitative research, is used to examine certain populations or samples, sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative with the aim of testing hypotheses. This study aims to analyze the effect of product quality and brand image on customer loyalty among consumers at The Don's House in Metro City. Data collection uses instruments in the form of interviews, questionnaires, and library research. The results of the study also show that product quality has a positive and significant influence on customer loyalty. It can be concluded that customer loyalty feels attracted to the quality of The Don's House products. the results of testing the hypothesis regarding the relationship between brand image and customer loyalty with the result that brand image has a positive and significant effect on customer loyalty. The results of simultaneous hypothesis testing regarding the relationship between product quality and brand image with customer loyalty with the result that product quality and brand image have a positive and significant effect on customer loyalty.